Locally Advanced Pancreatic Cancer - Oikonomopoulos, Georgios Michael; Huber, Kathryn E; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Treatment of locally advanced pancreatic cancer is palliative, based on chemotherapy and according to response, chemoradiotherapy can be applied. The authors summarize three abstracts (#LBA146, #256 and #303) presented on the 2013 ASCO Gastrointestinal Cancers Symposium, which were focused on treatment of locally advanced pancreatic cancer. A discussion is presented about the different chemotherapy or chemoradiotherapy regimens, that move away from gemcitabine-based treatment, and the effort to find less toxic, but efficient therapeutic combinations. Image: St. Savvas Anticancer Hospital. Athens, Greece.